KEWENANGAN PENGADILAN NEGERI DALAM MEMUTUS SENGKETA LELANG PERBANKAN SYARIAH - Grace Immanuel Limongan (Jurnal HUKUM BISNIS, 2019)
One of the important solutions that must be considered by the government in recovering Indonesian economy is implementing sharia economy. Sharia economy has a strong commitment on poverty alleviation, enforcement of justice, economical growth, elimination of usury and prohibition of currency speculation, thus creating economic stability. Sharia economy which emphasizes justice, teaches concepts that excel in dealing with monetary turmoil compared to conventional systems. This fact has been widely acknowledged by many global economic experts, such as Rodney Shakespeare (United Kingdom), Volker Nienhaus (Germany), etc. Going forward, government must pay more attention to the sharia economy system that has been proven to be effective and more resistant in crisis. Sharia economy system represented by sharia banking institutions have shown to be resilience since it uses a profit sharing system, so that it does not experience negative spread as other conventional banks are. In fact, sharia banking grows in difficult times.Meanwhile, large banks experienced severe downturn which ended in liquidation, some other conventional banks were forced to be recapitulated by the government in a large amount. The budget funds that should be prioritized alleviate people’s poverty, was used to help conventional banks. This is the fact that happens when still using and hold ribawi sharia economics. Therefore, the government is now more concerned with the development of sharia economics in Indonesia, both through ratification of laws and by establishing sharia financial institutions